BITCOIN DI INDONESIA: SELAIN HARAM, ANCAMANKAH TERHADAP LINGKUNGAN? - Alfian Alfian (Journal of Sharia Economics, 2022)
Bitcoin is the first cryptocurrency that is widely accessible and the most sought after by investors working in the Cryptocurrency world. At the same time, the price of Bitcoin continues to fluctuate, raising concerns about inflation and monetary aggregates in Indonesia. Therefore, Bank Indonesia (BI) prohibits financial institutions in Indonesia from using cryptocurrencies as a means of payment or financial services. This is also supported by the Indonesian Ulema Council (MUI) institution by prohibiting the use of cryptocurrencies in Indonesia. Apart from the policies of Bank Indonesia and the MUI, there are several factors that cause the use of cryptocurrencies to be prohibited in Indonesia, including having a negative impact on the economy and the environment. Keyword: Cryptocurrency; Bitcoin; Indonesian policy; environmental impact.